Improving Care Pathways for Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention - Amin, Amit P. (Am J Cardiol, 2019)
Acute coronary syndrome (ACS) admissions are common and costly. The association between comprehensive ACS care pathways, outcomes and costs are lacking. From 434,172 low-risk, uncomplicated ACS patients eligible for early discharge (STEMI 35%, UA/NSTEMI 65%) from the Premier database, we identified ACS care pathways, stratified STEMI vs. UA/NSTEMI, that included access site for PCI (trans-radial intervention (TRI) vs. trans-femoral intervention (TFI)) and length of stay (LOS). Associations with costs and outcomes (death, bleeding, acute kidney injury and myocardial infarction at 1-year) were tested using hierarchical, mixed-effects regression and projections of cost-savings with change in care pathways were obtained using modeling. In low-risk uncomplicated STEMI patients, compared with TFI and LOS≥3 days, a strategy of TRI with LOS<3 days and TFI with LOS<3 days were associated with cost-savings of $6,206 and $4,802, respectively. Corresponding cost-savings for UA/NSTEMI patients were $7,475 and $6,169, respectively. These care-pathways did not show an excess risk of adverse outcomes. We estimated that >$300 million could be saved if prevalence of the TRI with LOS<3 days and TFI with LOS<3 days strategies are modestly increased to 20% and 70%, respectively. In conclusion, we demonstrate the potential opportunity of cost-savings by repositioning ACS care pathways in low-risk and uncomplicated ACS patients, towards transradial access and a shorter LOS without an increased risk of adverse outcomes.